2021
DOI: 10.13057/biodiv/d220262
|View full text |Cite
|
Sign up to set email alerts
|

The endophytic fungi from South Sumatra (Indonesia) and their pathogenecity against the new invasive fall armyworm, Spodoptera frugiperda

Abstract: Abstract. Gustianingtyas M, Herlinda S, Suwandi. 2021. The endophytic fungi from South Sumatra (Indonesia) and their pathogenicity against the new invasive fall armyworm, Spodoptera frugiperda. Biodiversitas 22: 1051-1062. Maize in Indonesia is currently experiencing attacks and outbreaks of the new invasive fall armyworm, Spodoptera frugiperda. The S. frugiperda larvae emerge from the leaf midrib when eating, after hiding in the maize stalk so that it is difficult to control by contact. This study aimed to fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 43 publications
2
24
0
Order By: Relevance
“…However, the compatibility of EPFs with FAW pheromones and their impact on fertility and egg viability highlight the potential for the development of lure and infect application strategies (Rivero-Borja et al 2018;Gutiérrez-Cárdenas et al 2019;Akutse et al 2020b). Furthermore, endophytic colonization of cereals and other hosts with B. bassiana, M. anisopliae, and Metarhizium robertsii (Metchnikoff) Sorokin, and the impact of such plant colonization on FAW survival, growth, reproduction, and food preference offer a promising potential for incorporating EPFs into FAW management practices (Ramirez-Rodriguez & Sanchez-Pena 2016;Jaber & Ownley 2018;Vega 2018;Mwamburi 2021;Russo et al 2021;Gustianingtyas et al 2021).…”
Section: Entomopathogenic Fungimentioning
confidence: 99%
“…However, the compatibility of EPFs with FAW pheromones and their impact on fertility and egg viability highlight the potential for the development of lure and infect application strategies (Rivero-Borja et al 2018;Gutiérrez-Cárdenas et al 2019;Akutse et al 2020b). Furthermore, endophytic colonization of cereals and other hosts with B. bassiana, M. anisopliae, and Metarhizium robertsii (Metchnikoff) Sorokin, and the impact of such plant colonization on FAW survival, growth, reproduction, and food preference offer a promising potential for incorporating EPFs into FAW management practices (Ramirez-Rodriguez & Sanchez-Pena 2016;Jaber & Ownley 2018;Vega 2018;Mwamburi 2021;Russo et al 2021;Gustianingtyas et al 2021).…”
Section: Entomopathogenic Fungimentioning
confidence: 99%
“…The larval stage of this pest eats leaves, stems, flowers, fruits, and growing points (Montezano et al 2018). The larvae are found on the surface of maize leaves or stalks in the morning and then hide in the leaf's midribs at daylight (Gustianingtyas et al 2021), and this behavior makes the FAW larvae difficult to be controlled.…”
Section: Introductionmentioning
confidence: 99%
“…The fungal secondary metabolites are produced by blastospores in insect hemolymph and disrupted the normal cell metabolism (Mancillas-Paredes et al 2019), and then, the toxins produced by the metabolites kill the insects (El-Ghany 2015). Our previous study showed that the endophytic fungi could decrease the leaf consumption by the S. frugiperda larvae resulting in larval weight loss and low survival (Gustianingtyas et al 2021). The reduction in leaf area consumed by the larvae treated with the endophytes is caused by antifeedant or deterrent properties of in planta-produced B. bassiana metabolites (Russo et al 2020).…”
Section: Development Of Spodoptera Frugiperda Fed On Young Maize Colo...mentioning
confidence: 99%
“…However, in the field, the larvae occurred on the surface of leaves or maize stalks only in the morning, but at daylight up to night, they hide in the corn midribs (Herlinda et al 2021). So, topical application of the fungus against the S. frugiperda larvae is less effective (Gustianingtyas et al 2021). To control such hiding larvae in the field, the fungi colonizing in plant tissues or endophytic fungi are needed (Ramos et al 2020).…”
mentioning
confidence: 99%
See 1 more Smart Citation